Better banking regulation for Brazil: regulatory impact analysis in the financial sector - Silva, Gabriela Borges (2024)
Central banks, including the Brazilian Central Bank (BCB), are pivotal in mitigating economic crises and adapting to digital transformations. The dynamic nature of global financial systems requires robust regulatory frameworks within these institutions to ensure effective governance and accountability. This thesis provides a comprehensive analysis of the integration of Regulatory Impact Analysis (RIA) into Brazil's National Financial System, focusing specifically on its implementation within the Brazilian Central Bank (BCB) and the National Monetary Council (CMN). Regulatory Impact Analysis (RIA) has been gaining increasing importance for Brazilian Administrative Law, especially after the enactment of two laws and a presidential decree that made its use mandatory in regulatory policy formulation. Since October 14, 2021, the BCB and the CMN, the banking regulatory authorities in Brazil, have been legally compelled to use RIA as a requirement for policymaking. The study adopts a mixed-methods approach, utilizing empirical evidence, comparative insights, and case studies to evaluate the impact of RIA on financial regulation. It focuses on the Brazilian context, comparing it with established U.S. and EU practices. The findings suggest that while RIA has been formally adopted in Brazil, its practical application remains limited and varies significantly in depth and rigor. The research identifies challenges such as the lack of comprehensive training for stakeholders involved in conducting RIAs, as well as the need for greater transparency and stakeholder engagement in the RIA process. Despite these challenges, the evidence points to a gradual improvement in regulatory quality and decision-making processes due to the implementation of RIA. This thesis contributes to the literature on financial regulation by providing an examination of the role of RIA in enhancing regulatory frameworks within central banks. It offers insights into the conditions under which RIA can improve decision-making and underscores the importance of adaptability and continuous learning in regulatory practices. By highlighting the potential of RIA to bridge existing gaps in systematic evaluation, the study advocates for a reflexive approach to RIA, one that accommodates the dynamic and complex nature of financial markets.